2009
DOI: 10.1007/s00213-009-1600-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the metabotropic glutamate antagonist MPEP on striatal expression of the Homer family proteins in levodopa-treated hemiparkinsonian rats

Abstract: These results suggest that Homer protein family is not causally involved in the development of dyskinetic movements induced by levodopa treatment in this animal model of parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 95 publications
(99 reference statements)
1
5
0
Order By: Relevance
“…The administration of MPEP alone did not modify any of both markers. As previously shown, we found that the mGluR5 glutamate antagonist, MPEP reduced the dyskinetic movements elicited by levodopa treatment in 6‐OHDA‐lesioned rats and MPTP‐treated monkeys (Dekundy et al, 2006; Jiménez et al, 2009; Levandis et al, 2008; Mela et al, 2007; Morin et al, 2010). An attenuation of dyskinesias has also been observed in these models using other mGluR5 antagonists such as 3‐[(2‐methyl‐1,3‐thiazol‐4‐yl)ethynyl]pyridine (MTEP) (Gravius et al, 2008; Morin et al, 2010) In agreement with previous reports, we observed that striatal VGlut1 and VGlut2 were not different between intact and lesioned side in 6‐OHDA‐lesioned rats (Chung et al, 2006; Massie et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The administration of MPEP alone did not modify any of both markers. As previously shown, we found that the mGluR5 glutamate antagonist, MPEP reduced the dyskinetic movements elicited by levodopa treatment in 6‐OHDA‐lesioned rats and MPTP‐treated monkeys (Dekundy et al, 2006; Jiménez et al, 2009; Levandis et al, 2008; Mela et al, 2007; Morin et al, 2010). An attenuation of dyskinesias has also been observed in these models using other mGluR5 antagonists such as 3‐[(2‐methyl‐1,3‐thiazol‐4‐yl)ethynyl]pyridine (MTEP) (Gravius et al, 2008; Morin et al, 2010) In agreement with previous reports, we observed that striatal VGlut1 and VGlut2 were not different between intact and lesioned side in 6‐OHDA‐lesioned rats (Chung et al, 2006; Massie et al, 2010).…”
Section: Discussionsupporting
confidence: 61%
“…Brain glutamate overactivity is well documented in PD and antiglutamatergic drugs have been proposed to relieve PD symptoms and attenuate levodopa‐induced motor complications (Calon et al, 2003; Chase et al, 1996; Engber et al, 1994; Gubellini et al, 2006; Jiménez et al, 2009; Marin et al, 2000, 2001). It has been reported that metabotropic GluR5 specific binding is increased in the basal ganglia of parkinsonian monkeys that developed dyskinesias following chronic levodopa treatment (Samadi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of double injection coordinates is a more recent phenomenon, often carried out in laboratories that have previously used single injection protocols, presumably in response to a similar drop off in lesion success to that seen in our laboratory (a conclusion supported by personal communications). The coordinates used by Jiménez et al (2009) are very close to those presented in the current work (allowing for the use of skull surface for the depth coordinate), including the use of a low nose-bar position.…”
Section: Discussionmentioning
confidence: 87%